Catching them Young — Nurturing Primary Students into Global Citizens - Pethiya, Sangeeta (THE PRIMARY TEACHER, 2018)
Global Citizenship Education (GCED) aims to transform students into global citizens by developing core competencies in them, allowing them to actively engage with the world, and making it a more just and sustainable place to live in. This paper underlines that education is not only about obtaining high scores in examination but involves in-depth knowledge and insightful learning as well, especially, at a time, when the students have easy access to a vast array of information available online. Teachers, who are the most effective interface between students and knowledge, play a crucial role in shaping these young minds, many of whom may emerge as future leaders. Therefore, they need to be skilful, updated at all times, and use teaching–learning methodologies or strategies to ensure maximum learning. This paper also tries to bring forth some of the best teaching–learning practices, including ‘blended learning’, that may be implemented in classrooms